The effect of income on mortality: New evidence for the absence of a causal link - Alexander Ahammer; G. Thomas Horvath; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2015)
We analyze the effect of income on mortality in Austria using administrative social security data. To tackle potential endogeneity concerns arising in this context, we estimate time-invariant firm-specific wage components and use them as instruments for actual wages. While we do find quantitatively small yet statistically significant effects in our naïve least squares estimations, IV regressions reveal a robust zero-effect of income on ten-year death rates for prime-age workers, both in terms of coefficient magnitude and statistical significance. These results are robust to a number of different sample specifications and both linear and non-linear estimation methods.
Keywords: J14; J31; I10; 330; Income; mortality; wage decomposition